Introduction to comparative law - Zweigert, Konrad (Clarendon Press, 1998)
This third edition of the modern classic Zweigert &​ Kotz's Introduction to Comparative Law is fully revised and updated, but its familiar structure and easy style remain the same. The book first discusses the nature of Comparative Law, its functions, aims, methods and history, and then it surveys the main features of the major legal families of the world.